Effect of Combined Kinetic chain exercise with Functional task training in Postmenopausal Women with knee osteoarthritis: A Case report - Nidhi Suresh Sharma; Vikas Kumar Lamba; Krishna Kumar Singh; Amar Damle (The Bioscan, 2025)
Introduction: Osteoarthritis [OA] is a progressive degenerative joint disease that affects all structures of the joint. OA can affect all joints, but the most common sites are the knee, the hip and the hand. OA is an extremely prevalent rheumatic musculoskeletal disorder that affected 303 million people worldwide in 2017. Menopause is defined as the irreversible discontinuance of menstrual period due to associated decreasing ovarian functions. Case Description: We are addressing the case of a 55-year-old postmenopausal women housewife she was a farmer. The patient was started a gradually pain in her right knee since 3 years and was aggravated since 15 days who had Osteoarthritis in her right knee. We created a 12 weeks treatment plan for this patient that incorporates a number of advanced therapy techniques, including closed kinetic chain exercise with Functional task training for exercise session. We created a through rehabilitation Programme for out Patient, who had osteoarthritis in her knee, & worked incredibly well. We assessed the efficacy of our outcomes measures using a variety of outcome, including WOMAC, KOOS score, NPRS and MMT. It was found to be more beneficial to provide modern Physiotherapy approaches for improving the overall health & quality of life of the patient.